STRATEGI PEMERINTAH DAERAH KABUPATEN KOLAKA DALAM PENGELOLAAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY (CSR) - Jony Puspa Kusuma; Andi Lopa Ginting (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
The existence of a mining company for the community is considered quite detrimental and leads to negative things, especially with all forms of natural exploitation and processing that can cause environmental damage which is very worrying for the people living around it. Corporate Social Responsibility (CSR) is one of the obligations that must be carried out by companies from the impacts that have been caused to society and the environment. Based on the Laws and Government Regulations governing CSR, local governments have an important role in the management and implementation of CSR funds in the community so that they can provide benefits to the local community, sustainably and in line with the development objectives of the regional government programs. The focus of this study is to determine the strategy of the Kolaka Regency local government in implementing CSR program management in Kolaka Regency using a SWOT analysis. This research is a qualitative descriptive study. The implementation of the CSR program carried out by the Regional Government together with the Company to the Kolaka Regency Community has not been optimal. The impact of the CSR Program on Community Welfare in Kolaka Regency is only felt by the people who live around the Company